Axially Chiral Cannabinols: A New Platform for Cannabinoid‐Inspired Drug Discovery. (16th March 2020) - Navaratne, Primali V.; Wilkerson, Jenny L.; Ranasinghe, Kavindri D.; Semenova, Evgeniya; Felix, Jasmine S.; Ghiviriga, Ion; Roitberg, Adrian; McMahon, Lance R.; Grenning, Alexander J.
Abstract: Phytocannabinoids (and synthetic analogs thereof) are gaining significant attention as promising leads in modern medicine. Considering this, new directions for the design of phytocannabinoid‐inspired molecules is of immediate interest. In this regard, we have hypothesized that axially‐chiral‐cannabinols (ax‐CBNs), unnatural and unknown isomers of cannabinol (CBN) may be valuable scaffolds for cannabinoid‐inspired drug discovery. There are two main factors directing our interest to these scaffolds: (a) ax‐CBNs would have ground‐state three‐dimensionality; ligand‐receptor interactions can be more significant with complimentary 3D‐topology, and (b) ax‐CBNs at their core structure are biaryl molecules, generally attractive platforms for pharmaceutical development due to their ease of functionalization and stability. Herein we report a synthesis of ax‐CBNs, examine physical properties experimentally and computationally, and perform a comparative analysis of ax‐CBN and THC in mice behavioral studies. Abstract : A new twist for cannabinoid research : We report a strategy to conformationally bias cannabinol (CBN) scaffolds in a three‐dimensional orientation. CBN C‐9 to C‐10 methyl transposition yields axially‐chiral cannabinols ( ax ‐CBNs), unnatural isomers of CBN that are comprised of the pharmaceutically relevant biaryl framework and display ground state three‐dimensionality due to steric hinderance. The conformationally biased scaffolds may provide new directions for cannabinoid‐inspired drug discovery.